Alveolarization in Hong Kong Cantonese: a sociophonetic study of neogrammarian and lexical diffusion models of sound change - Chan, M (2017)
This thesis is a quantitative study of sociophonetic variation which focuses on the Hong Kong Cantonese velar coda consonants -η and -k. These codas have, under certain linguistic contexts, become increasingly realized as alveolar nasal and oral stop consonants, [-n] and [-t], respectively. For the purpose of this thesis, the phenomenon of sound shift from -η and -k, to [-n] and [-t] respectively will be termed 'alveolarization'. Insofar as the language of a speech community is a shared vehicle for communication and sound changes are constrained by the need for mutual intelligibility, the central aim of this thesis is to uncover the factors which contribute the most to driving this sound change. In describing the variation in these consonants, I examine the concomitant social and linguistic factors which might help explain it. While this study focuses on one specific set of linguistic variables, it aims to analyse a broad set of factors to obtain a picture of the complexity of this sound change. The sound change is of theoretical interest as it provides an opportunity to evaluate the neogrammarian regularity hypothesis and the lexical diffusion model of sound change. The neogrammarian regularity hypothesis states that sound changes are regular and admit no exceptions—they are purely driven by phonological context and show no lexical variation. On the other hand, the lexical diffusion model predicts that sound changes progress through the lexicon in a gradual manner. By examining the effects of neighbouring phonological environment on the velar codas, and by analyzing which lexemes might be leading the change, as well as whether there are any lexical frequency effects, this thesis sets out to test both models of sound change.